2012
DOI: 10.1098/rsta.2012.0028
|View full text |Cite
|
Sign up to set email alerts
|

Temperature changes and energy inputs in giant planet atmospheres: what we are learning from H 3 +

Abstract: Since its discovery at Jupiter in 1988, emission from H + 3 has been used as a valuable diagnostic tool in our understanding of the upper atmospheres of the giant planets. One of the lasting questions we have about the giant planets is why the measured upper atmosphere temperatures are always consistently hotter than the temperatures expected from solar heating alone. Here, we describe how H at Saturn and the first profile of H + 3 emission at Uranus not significantly distorted by the effects of the Earth's at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Our results can also be compared to the thermospheric temperatures derived from the Cassini UVIS solar and stellar occultations (Shemansky and Liu, 2012;Koskinen et al, 2013) and to temperatures inferred from auroral H 3 + emission (e.g., Melin et al, 2007Melin et al, , 2011Stallard et al, 2012;O'Donoghue et al, 2014). The temperatures at the highest altitudes of the Voyager 2 solar ingress occultation are derived from the H 2 densities determined from the H 2 Smith et al (1983) and Hubbard et al (1997).…”
Section: Further Considerations From the Data Retrievalsmentioning
confidence: 85%
See 1 more Smart Citation
“…Our results can also be compared to the thermospheric temperatures derived from the Cassini UVIS solar and stellar occultations (Shemansky and Liu, 2012;Koskinen et al, 2013) and to temperatures inferred from auroral H 3 + emission (e.g., Melin et al, 2007Melin et al, , 2011Stallard et al, 2012;O'Donoghue et al, 2014). The temperatures at the highest altitudes of the Voyager 2 solar ingress occultation are derived from the H 2 densities determined from the H 2 Smith et al (1983) and Hubbard et al (1997).…”
Section: Further Considerations From the Data Retrievalsmentioning
confidence: 85%
“…Note that although we expect the mean molecular mass to drop off with altitude, the exact profile will depend on uncertain vertical transport parameters. Miller et al, 2000;Hallett et al, 2005a;Melin et al, 2007Melin et al, , 2011Gustin et al, 2009;Stallard et al, 2012;O'Donoghue et al, 2014) have provided our only constraints on the atmospheric density/temperature structure in Saturn's thermosphere and mesopause region. However, deriving temperatures and densities from these methods requires several assumptions about atmospheric properties that are not well known.…”
Section: Occultationmentioning
confidence: 93%
“…High latitude temperatures in Saturn's upper atmosphere published until recently had values below $460 K (Melin et al, 2007;Vervack and Moses, 2012), but Melin et al (2011) andStallard et al (2012) have shown that H þ 3 emission may be brighter than previously indicated, and temperatures hotter. Using high resolution Cassini Visual and Infrared Mapping Spectrometer (VIMS) images, Melin et al (2011) inferred temperatures of a segment of the auroral oval of 440 ± 50 K. Even higher temperatures in Saturn's auroral oval of (563-624) ± 30 K were derived from Cassini VIMS observations by Stallard et al (2012), so auroral temperatures on Saturn up to around 650 K are within the observed range.…”
Section: Sensitivity To Magnetospheric Forcing Parametersmentioning
confidence: 91%
“…Using high resolution Cassini Visual and Infrared Mapping Spectrometer (VIMS) images, Melin et al (2011) inferred temperatures of a segment of the auroral oval of 440 ± 50 K. Even higher temperatures in Saturn's auroral oval of (563-624) ± 30 K were derived from Cassini VIMS observations by Stallard et al (2012), so auroral temperatures on Saturn up to around 650 K are within the observed range. The thick red line in the upper panel Fig.…”
Section: Sensitivity To Magnetospheric Forcing Parametersmentioning
confidence: 94%
“…The three outer planets are the only objects that are close enough to us that their pole-to-pole profiles are observable with spatial resolution. Stallard et al [63] present the remarkable differences in pole-to-pole profiles of H + 3 emission from Jupiter, Saturn and Uranus and hence their magnetohydrodynamic activities; they involve similar processes but with different dominance. In all these three ionospheres, significant temporal variations of the emission intensity in variable time scales are observed, indicating the variations of the plasma temperature.…”
Section: Planetary Ionospheresmentioning
confidence: 99%